Remember that function composition is not function

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: on By evaluate we mean one of two things depending on what is in the parenthesis. If there is a number in the parenthesis then we want a number. If there is an x (or no parenthesis, since that implies and x) then we will perform the operation and simplify as much as possible. (a) ( f + g ) ( 4) In this case we’ve got a number so we need to do some function evaluation. ( f + g ) ( 4) = f ( 4) + g ( 4) = ( 2 + 3 ( 4 ) - 42 ) + ( 2 ( 4 ) - 1) = -2 + 7 =5 [Return to Problems] © 2007 Paul Dawkins 190 http://tutorial.math.lamar.edu/terms.aspx College Algebra (b) g - f Here we don’t have an x or a number so this implies the same thing as if there were an x in parenthesis. Therefore, we’ll subtract the two functions and simplify. Note as well that this is written in the opposite order from the definitions above, but it works the same way. g - f = g ( x) - f ( x) = 2 x - 1 - ( 2 + 3x - x 2 ) = 2 x - 1 - 2 - 3x + x 2 = x2 - x - 3 (c) [Return to Problems] ( fg ) ( x ) As with the last part this has an x in the parenthesis so we’ll multiply and then simplify. ( fg ) ( x ) = f ( x ) g ( x ) = ( 2 + 3 x - x 2 ) ( 2 x - 1) = 4 x + 6 x 2 - 2 x3 - 2 - 3x + x 2 = -2 x 3 + 7 x 2 + x - 2 [Return to Problems...
View Full Document

This note was uploaded on 06/06/2012 for the course ICT 4 taught by Professor Mrvinh during the Spring '12 term at Hanoi University of Technology.

Ask a homework question - tutors are online